Loen et Voltaire : une controverse métaphysique - Catherine Julliard (Recherches Germaniques)
The study concerns Loen’s reception of Voltaire’s thirteenth Lettre philosophique (Sur M. Locke), published in two letters in a magazine in French language, Les Amusemens littéraires, in 1741. It reveals the importance of metaphysical debates and the power of argumentative and polemical speeches during the Enlightenment, when different reflections on the notion of soul were clashing. The first part presents the ideological foundations of Voltaire’s Lettre. The second part examines Loen’s position in his two French letters : rejection at first, followed by a brutal reversal of his position. The last part analyses Loen’s violent refutation of Voltaire, published in the Kleine Schriften in 1751.